In vitro evaluation of aqueous seed extract of Psoralea corylifolia L. on seed germination and seedling vigour of maize - Kiran. B, Lalitha.V, Raveesha.K.A (Journal of Applied Pharmaceutical Science)
Aqueous seed extract of seeds of P.corylifolia were evaluated for seed germination and vigour index at 10, 20, 30, 40 and 50% concentration for 3,6, 12 and 24hours of treatment in maize seeds. Maximum and significant activity was observed in 20% concentration at 12hours of duration and recorded 88.0% germination and 1398.5 vogour index. Compared to control, it was recorded 72.1% germination and 1010.1 vigour index. In 30 and 40% concentration at 12 hours of duration, significant activity was recorded. In 6 hours of duration, moderate activity was observed in 10, 20, 30 and 40% concentration. No significant activity was observed in 3 hours and 24 hours duration at 10, 20, 30, 40 and 50% concentration of aqueous seed extract
Keywords: Psoralea corylifolia, Maize, Germination, Vigour Index